Pruning and training fruit trees - Somerville, Warren (Australia : Inkata Press, 1996)
The selection of suitable cultivator and rootstock combinations is the starting point for ongoing tree training and pruning. This book discusses the ways in which different fruit trees grow and respond to pruning. Training methods, thinning, harvesting and pest/disease control are examined.
Includes index
Primary
Keywords: Fruit pruning; Espaliers; Fruit -- Training